Arc‐nascent back‐arc signature in metabasalts from the Neoarchaean Jonnagiri greenstone terrane, Eastern Dharwar Craton, India. (10th July 2014) - Manikyamba, C.; Ganguly, Sohini; Santosh, M.; Singh, M. Rajanikanta; Saha, Abhishek
<x xml:space="preserve">Abstract</x> The Neoarchaean Jonnagiri greenstone terrane (JGT) is located at the centre of the arcuate Hutti–Jonnagiri–Kadiri–Kolar composite greenstone belt in the eastern Dharwar Craton. High MgO (MgO = 14 wt.%; Nb = 0.2 ppm), low Nb (LNB) (MgO = 7.8–12 wt.%; Nb = 0.1–5.1 ppm) and high Nb basalts (HNB) (MgO = 5.6–10.1 wt.%; Nb = 9.0–10.6 ppm) metamorphosed to lower amphibolite facies are identified based on their geochemical compositions. These metabasalts exhibit depleted HFSE (Nb–Ta, Zr–Hf), pronounced LREE and LILE enrichments suggesting contribution from subduction‐related components during their genesis. Th and U enrichment over Nb–Ta indicates influx of fluids dehydrated from subducted oceanic lithosphere. The high MgO basalts with higher Mg# (51) than that of the associated LNB and HNB (Mg# = 34–47) represent early fractionated melts of subduction‐modified mantle peridotite. The LNB were produced by partial melting of mantle wedge metasomatized by slab‐dehydrated fluids, whereas the HNB represents melts of subducted oceanic crust and hybridized mantle wedge. Lower Dy/Yb and variable La/Yb ratios suggest their generation at shallower depth within spinel peridotite stability field. The low Ce–Yb trend of these metabasalts reflects intraoceanic type subduction which straddles the fields of arc and back‐arc basin basalts, resembling the Mariana‐type arc basalts. The Jonnagiri metabasalts were derived in a paired arc‐back‐arc setting marked by nascent back‐arc rift system that developed in the proximity of an intraoceanic arc. Copyright © 2014 John Wiley & Sons, Ltd.